El derecho a la vida frente al derecho a la libertad de religión en el caso de las transfusiones sanguíneas en tratamientos médicos en niños y niñas testigos de jehová, en el Ecuador durante el 2017. - Román López, Damián Agustín (2021)
This article analyzes the right to life and freedom of religion, in the context of the medical procedure of blood transfusion to boys and girls belonging to Jehovah's Witnesses. The lex artis of many hospitals and clinics implements old procedures for blood transfusion and blood products without making use of modern technology, this causes a struggle for fundamental rights that not only cause legal problems that undermine the rights of the religious group, but also generates ethical uncertainties for health personnel. Therefore, the analysis not only seeks to weigh the conflict of fundamental rights but also to closely analyze the problem for Jehovah's Witnesses.